KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATERI BILANGAN PECAHAN BIASA DAN CAMPURAN - QUEEN TITAH WIDI ISLAMI; Yumi Sarassanti; NURUL APSARI (AL KHAWARIZMI: Jurnal Pendidikan Matematika, 2022)
Abstract: This study aims to describe students' mathematical communication skills in the material of ordinary and mixed fractions. The research subject is the seventh grade students of SMP Negeri 2 Nanga Pinoh and the object of this research is the students' mathematical communication skills. The type of research used in this research is descriptive qualitative research usingsurvey research methods. The instrument used is in the form of 3 test questions of mathematical communication skills in the form of descriptions. Research result obtained from the student's communication ability test showed that 43.5% of students answered according to the indicator of mathematical communication ability in writing and categorized as low and 63.05% of students answered according to the indicator of mathematical expression of communication ability and was categorized as moderate.Keywords: Mathematical Communication, Fractions Abstrak: Penelitian ini bertujuan untuk mendeskripsikan kemampuan komunikasi matematis siswa pada materi bilangan pecahan biasa dan campuran. Dengan subjek penelitian adalah siswa kelas VII SMP Negeri 2 Nanga pinoh dan objek dalam penelitian ini adalah kemampuan komunikasi matematis siswa. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian deskriptif kualitatif dengan menggunakan metode penelitian survey. Adapun instrumen yang digunakan yaitu berupa 3 soal tes kemampuan komunikasi matematis berbentuk uraian. Hasil penelitian diperoleh dari tes kemampuan komunikasi siswa menunjukan bahwa 43,5% siswa menjawab sesuai indikator kemampuan komunikasi matematis menulis dan dikategorikan rendah serta 63,05% siswa menjawab sesuai indikator kemampuan komunikasi matematis ekspresi dan dikategorikan sedang.Kata Kunci: Komunikasi Matematis, Bilangan Pecahan